Perbandingan hasil belajar siswa menggunakan media video pembelajaran dengan powerpoint berbasis contextual teaching and learning di SMA - Lusi Oktavia; Akmam Akmam; Desnita Desnita; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2020)
Learning media in the form of instructional videos and PowerPoint are currently being developed. Previous researchers said that the two media were good for use in physics lessons, but between the two media it was not yet known which one was good for material on Newton's Law of Gravity, Work, and Energy. Based on the explanation above learning media is important so the researcher want to do a research which purpose to compare between the use of video and Powerpoint.This study aims to determine the differences on the student learning outcomes by applying the learning video and CTL-based PowerPoint on the Newton Gravity Law and Work Energy materials at Grade X SMA Adabiah 2 Padang. This type of research was a quasi-experimental research. The research design was the Random Posttest only Control-Group Design. The population of this research was the students Grade X. A purposive sampling technique was used to take the sample of this research. The sample of this research consisted of 2 classes. This research only focused on the aspects of cognitive and psychomotor. The assessment instruments were in the form of learning outcomes test sheets and observation sheets for the aspects of psychomotor. The data obtained were analyzed by using the t test. The results showed that the mean score of the students’ competence in the aspect of cognitive of the class which used CTL-based PowerPoint learning method was higher than the class using CTL-based learning videos by using the statistical t test. It was obtained  tcount= 2,1009 and ttable = 2,0032.  The mean score of the students’ competence in the aspect of psychomotor of the class of using PowerPoint was higher than the class using the learning video. Thus, it can be concluded that there are significant differences on the student learning outcomes using the learning video and Contextual Teaching and Learning (CTL)-based PowerPoint of the science students Grade X of SMA Adabiah 2 Padang.